Multimedia-Based Learning Module Development for a Special Topics in Multimedia Course: A Four-D Research and Development Study - Riska; Muhammad Yahya; Muhammad Riska (PT. Global Research Collaboration, 2026)
Background/Context: The development of information and communication technology has promoted the use of multimedia-based learning in higher education to improve student engagement and independent learning. However, instructional materials for the Special Topics in Multimedia course were unsystematically organized, fragmented, and lacked structured learning modules, making it difficult for students to understand the content independently. Objective/Purpose: This study aimed to develop a systematically designed multimedia-based learning module for the Special Topics in Multimedia course to support structured learning and enhance student understanding. Method: This study employed a Research and Development approach using a four-D (4D) development model consisting of Define, Design, Develop, and Disseminate. The module was validated by material and media experts and tested through small and large group trials with students. Results: The developed module was evaluated as highly feasible by both material and media experts. Student trials indicated very positive responses, showing that the module was practical, easy to use, and supported effective independent learning. Conclusion: The multimedia-based learning module was proven to be valid, practical, and well-accepted by students. It successfully provides structured instructional materials and enhances independent learning, making it suitable for use in higher education.